Accuracy of Barrett Versus Third Generation Intraocular Lens Formula Across all Axial Lengths in Indian Eyes (Global Journal of Medical Research, 2020)
Purpose: To evaluate and compare the accuracy of Barrett Versus 3 rd generation formulae for different intraocular lens (IOL) powers for Indian eyes with different axial lengths.